Kontrol Diri dengan Tingkat Agresivitas Remaja yang Memiliki Orang Tua TNI atau POLRI - Khoir, Ansih Mahliyatul (Cognicia, 2019)
Aggressive behavior in adolescents can be minimized and reduced by using self-control. Self-control is needed for every individual, especially adolescents. Age and family’s environment are the factors that underlie a person can control himself. The aims of this research are to knowing the relationship between self-control and the level of aggressiveness in adolescents who have TNI or POLRI parents. This research using quantitative correlational approarch with the data collections using quota sampling technique, the subjects of this research were aged 13 until 17 years old who have TNI or POLRI parents. The instrument of this research using self control scale from Tangney, Baumeister, and Boone theory, and also using aggressive scale from Baron. The results of this study showed that there was a significant negative relationship between self-control and the level of aggressiveness in adolescents who have TNI or POLRI parents. It means, the increasing of self-control possessed by adolescents, the level of aggressiveness will be decreases, in another hand the decreasing of self-control that teenager has, the level of aggressiveness will be increases.